Validation of a gender-specific binary depression screening version (GIDS-15) in two German samples - Pellowski, Jan S.; Ebert, David D.; Christiansen, Hanna (Frontiers in Psychiatry, 2025)
ObjectiveFindings from depression research increasingly suggest a gender-dependent clinical appearance of relevant symptoms. At the same time, there is a lack of gender-sensitive screening procedures in clinical practice to better identify hidden depression in men. The present study examines the factor structure and psychometric characteristics of the translated version of the Gender Inclusive Depression Scale (GIDS) based on two large German-speaking mixed-sex samples, and assess sex and age effects.MethodsThe preliminary exploratory validation of the German GIDS version was initially carried out using exploratory factor analysis with an online recruited non-clinical sample (N = 1173). The established factor structure was replicated with confirmatory factor analysis in a separate sample (participants of an alcohol prevention study; N = 418). Psychometric properties were calculated.ResultsThe exploratory factor analysis resulted in a 5-factor solution, and was confirmed in the second analysis. A screening version comprises 15 items. Overall, psychometric properties are satisfactory, with only two subscales (aggressiveness, substance use) with critical values. The majority of sex effects could be established.ConclusionsThe GIDS-15 is a solid, multidimensional depression screening instrument that should be complemented by a gender assessment tool. There is further evidence that the inclusion of additional criteria alters the gender ratio in depression screening. After further studies to validate the GIDS-15, implementation in primary care could be indicated. Gender beyond the binary should be analysed in further studies.